Contamination Des Eaux De Puits Par Les Salmonelles Et Les Vibrions non-O1/non-O139 Dans Les Quartiers Précaires Du Sixième Arrondissement De Cotonou (Sud-Bénin) - E.O., Hounsounou; L., Ayi-Fanou; A.C., Ayéna; Tchibozo M., Agassounon Djikpo; D., Mama (European Scientific Journal, ESJ, 2018)
The well waters are solicited for several uses in the households in the sixth district of Cotonou. In order to assess the contamination of these wells waters by some pathogenic germs, one hundred and twenty (120) samples were collected for four (4) seasonal campaigns (two rainy and two dry) at the rate of thirty (30) samples per season. The study has focused on the research of Salmonella and choleraic vibrios by using the referenced methods. The analysis results indicate the presence of salmonella sp. in 73.33 % (high rainy season) ; 56.67 % (high dry season) ; 43.33 % (small rainy season) and 40 % (small dry season) of well water samples. The strains of vibrios isolated do not agglutinate with serum anti-O1 and anti-O139. The burden in these nonO1/non-O139 vibrios in the waters varies from <1 to 10 CFU/100 ml. This pathogenic germ is identified in most of the well water (46.67 %) during the small dry season. These two pathogenic bacteria that are found out of standards in the water of the wells analyzed can cause minor or severe infections to the riparian population consumers.